Human capital in the Dubai hotel industry: A study of four- and five-star hotels and the HR challenges they face. Issue 2 (3rd April 2019) - Brien, Anthony; Anthonisz, Angela; Suhartanto, Dwi
Abstract: Dubai brands itself as an international leisure and business center and home to the luxury hotel market. While hotel growth has been, and continues to be rapid, little is known about hotel employees, their demographics or how they feel about working in this industry. This article reports the findings of what is the first review of Dubai hotel human capital, noting there are significant difference in workforce demographics to other countries, for example, it is male dominated, highly educated, and employees note positive levels of organizational social capital. It also highlights potential challenges going forward.